Flow analysis of individual blood extracellular vesicles in acute coronary syndrome. (17th February 2017) - Vagida, Murad; Arakelyan, Anush; Lebedeva, Anna; Grivel, Jean-Charles; Shpektor, Alexander; Vasilieva, Elena; Margolis, Leonid
Abstract: A diverse population of small extracellular vesicles (EVs) that are released by various cells has been characterized predominantly in bulk, a procedure whereby the individual characteristics of EVs are lost. Here, we used a new nanotechnology-based flow cytometric analysis to characterize the antigenic composition of individual EVs in patients with acute coronary syndrome (ACS). Plasma EVs were captured with 15-nm magnetic nanoparticles coupled to antibodies against CD31 (predominantly an endothelial marker), CD41a (a marker for platelets), and CD63 or MHC class I (common EV markers). The total amounts of EVs were higher in the ACS patients than in the controls, predominantly due to the contribution of patients with acute myocardial infarction. For all captured fractions, the differences in the EV amounts were restricted to CD41a + EVs. The increase in the numbers of EVs in the ACS patients, predominantly of platelet origin, probably reflects platelet activation and may indicate disease progression.